Cultural Patterns in Ilya Kormiltsev’s Poetry (Based on the Poem „Claws”) - Iavtseva, Anastasiia (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2019)
Rock poetry has been attracting scholarly attention in Russia since the late 20th century. As a phenomenon of world culture, it dates back to the 1960s; in the Russian cultural sphere, however, its beginnings are usually associated with the turn of the 21st century. The aim of the present paper is to decipher and interpret the cultural codes used by Ilya Kormiltsev in his texts (mostly known as lyrics of the songs performed by the band Nautilus Pompilius). This is done on basis of the poem Kogti [Claws].